1993
DOI: 10.1111/j.1540-8191.1993.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Conservation and Autotransfusion in Cardiac Surgery

Abstract: Blood conservation techniques of withdrawal of blood just before surgery, intraoperative blood salvage with Solcotrans (Solco Basle [UK] Ltd.), and profound hemodilution were used in 14 patients undergoing open heart surgery (group I) and compared with equally matched 14 patients who had profound hemodilution only during cardiopulmonary bypass (CPB) and acted as controls (group II). Group I patients required a mean of 255 mL of homologous blood per patient to achieve a target hemoglobin of 8 g/dL compared to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that the use of acute normovolaemic haemodilution with autologous blood transfusion reduces the transfusion rate of homologous packed red cells, fresh frozen plasma and platelet concentrates during cardiac surgery [1][2][3]. The blood-sparing effect of this technique is based on the fact that diluted blood is shed during surgery, when the greatest loss of intravascular fluid occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the use of acute normovolaemic haemodilution with autologous blood transfusion reduces the transfusion rate of homologous packed red cells, fresh frozen plasma and platelet concentrates during cardiac surgery [1][2][3]. The blood-sparing effect of this technique is based on the fact that diluted blood is shed during surgery, when the greatest loss of intravascular fluid occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 2. Changes in gastric mucosal pH phi A, gastric mucosal carbon dioxide tension pi-CO 2 B, and the difference between arterial pH and pHi pHa -pHi C during the study period in the two study groups.…”
mentioning
confidence: 99%